PENGARUH KESEJAHTERAAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN CIREBON TAHUN 2013 - Budiman, Andri (Agroswagati : Jurnal Agronomi, 2021)
This study examines the effects of welfare and motivation on employee performance at the Regional Secretariat of Cirebon Regency in 2014. The research aims to analyze the simultaneous and partial influence of welfare and motivation on employee performance. The hypothesis posits that welfare and motivation have no significant effect on employee performance in this institution. The study employs an explanatory survey method with path analysis, supported by a literature review. The variables consist of welfare (X1), motivation (X2), and employee performance (Y). The population includes all civil servants at the Regional Secretariat of Cirebon Regency as of May 2013, totaling 129 individuals, with random sampling used for data collection. The research instrument is a questionnaire, tested for validity and reliability beforehand. Data were transformed using the Method of Successive Intervals (MOSI) and analyzed through normality, homogeneity, F-test (simultaneous), and t-test (partial) analyses. The results indicate that welfare contributes 55.21% to performance, motivation accounts for 14.69%, and together, they explain 69.90% of performance variation. The remaining 30.10% is influenced by other unexamined variables. These findings demonstrate that welfare and motivation play a crucial and statistically significant role in enhancing employee performance at the Regional Secretariat of Cirebon Regency in 2014.